Efficacy and Safety of High-Power Short-Duration Radiofrequency Catheter Ablation of Atrial Fibrillation - Park, Je-Wook; Yang, Song-Yi; Kim, Min; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Whereas, high-power short-duration (HPSD) radiofrequency (RF) ablation is generally used in atrial fibrillation (AF) catheter ablation (CA), its efficacy, safety, and influence on autonomic function have not been well established in a large population. This study compared HPSD-AFCA and conventional power (ConvP)-AFCA in propensity score matched-population. Methods: In 3,045 consecutive patients who underwent AFCA, this study included 1,260 patients (73.9% male, 59 ± 10 years old, 58.2% paroxysmal type) after propensity score matching: 315 in 50~60W HPSD group vs. 945 in the ConvP group. This study investigated the procedural factors, complication rate, rhythm status, and 3-month heart rate variability (HRV) between the two groups and subgroups. Results: Procedure time was considerably short in the HPSD group (135 min in HPSD vs. 181 min in ConvP, p < 0.001) compared to ConvP group, but there was no significant difference in the complication rate (2.9% in HPSD vs. 3.7% in ConvP, p = 0.477) and the 3-month HRV between the two groups. At the one-year follow-up, there was no significant difference in rhythm outcomes between the two groups (Overall, Log-rank p = 0.885; anti-arrhythmic drug free, Log-rank p = 0.673). These efficacy and safety outcomes were consistently similar irrespective of the AF type or ablation lesion set. The Cox regression analysis showed that the left atrium volume index estimated by computed tomography (HR 1.01 [1.00–1.02]), p = 0.003) and extra-pulmonary vein triggers (HR 1.59 [1.03–2.44], p = 0.036) were independently associated with one-year clinical recurrence, whereas the HPSD ablation was not (HR 1.03 [0.73–1.44], p = 0.887). Conclusion: HPSD-AFCA notably reduced the procedure time with similar rhythm outcomes, complication rate, and influence on autonomic function as ConvP-AFCA, irrespective of the AF type or ablation lesion set.